(3hUjI GHf bJjHI Edi hdOgs - (3YHO Gddg Hf eSde Hf bJjHI GdOjnfnhQqj, CHh eMeO, GHf obnJrjnHI, J (B276 (3g` s
(3ChdgG (B:s
(3jG Hfj, ChUjc Cf JeScJ HgG, QLhJ dc GdfLGI, hEf GSJYedJ eG ajgG SYOJ Ef TGA Gddg s
(3BNQgG (B:s
(3habfG Gddg hEjGc deMGg hLejd ehGgHg, hLYdc CgdkC ddehYXI, hfaYc HgG JeJ GdhUjI dGHf bJjHI QMeg Gddg Ydjg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3fSNI fajSI HgG CKQ JbWjYs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B137s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B183 s
Keywords: (3GdCOHs